Composition of Free and Bound Phenolics from Paeonia suffruticosa Andr. Flowers and Their Antioxidant and α-Glucosidase inhibitory Activities - CHEN Ling, WANG Xuefang, LI Zhining, ZHANG Lipan, LI Xiao, NING Erjuan (Shipin Kexue, 2025)
Free phenolics (FP), esterified phenolics (EP), glycosidized phenolics (GP) and insoluble bound phenolics (IBP) were successively extracted from two varieties of peony flowers: Danfeng and Xiangyu. The contents of total phenolics, total flavonoids and the major components in different phenolics fractions were determined, and their antioxidant activity and α-glucosidase inhibitory activity were also studied. It was found that for the two varieties, the contents of total phenols (31.45 and 32.64 mg/g, respectively) and total flavonoids (41.11 and 40.67 mg/g, respectively) in FP were both the highest, followed by EP and GP, and the lower values were found in IBP. Each of the two FPs contained 17 components, with the major ones being resveratrol, 1,2,3,4,6-O-pentagalloylglucose and apigetrin. The major components of EP and GP were kaempferol-7-O-β-D-glucoside and apigetrin. The antioxidant activity of FP was the strongest among the four phenolics fractions. The 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH), 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) cation radical scavenging capacity and ferric reducing power of FP were 855.03, 367.10, and 230.54 µmol/g for Danfeng, and 499.06, 290.64, and 196.39 µmol/g for Xiangyu, respectively. For both varieties, FP exhibited the strongest inhibitory activity against α-glucosidase with half maximal inhibitory concentrations of 12.15 and 13.87 μg/mL, respectively. The research results are of reference significance for the utilization of polyphenols in Danfeng and Xiangyu.